Mindful Walking in Psychologically Distressed Individuals: A Randomized Controlled Trial. (31st July 2013) - Teut, M.; Roesner, E. J.; Ortiz, M.; Reese, F.; Binting, S.; Roll, S.; Fischer, H. F.; Michalsen, A.; Willich, S. N.; Brinkhaus, B.
Abstract : Background . The aim of this randomized, controlled study was to investigate the effectiveness of a mindful walking program in patients with high levels of perceived psychological distress. Methods . Participants aged between 18 and 65 years with moderate to high levels of perceived psychological distress were randomized to 8 sessions of mindful walking in 4 weeks (each 40 minutes walking, 10 minutes mindful walking, 10 minutes discussion) or to no study intervention (waiting group). Primary outcome parameter was the difference to baseline on Cohen's Perceived Stress Scale (CPSS) after 4 weeks between intervention and control. Results . Seventy-four participants were randomized in the study; 36 (32 female, 52.3 ± 8.6 years) were allocated to the intervention and 38 (35 female, 49.5 ± 8.8 years) to the control group. Adjusted CPSS differences after 4 weeks were −8.8 [95% CI: −10.8; −6.8] (mean 24.2 [22.2; 26.2]) in the intervention group and −1.0 [−2.9; 0.9] (mean 32.0 [30.1; 33.9]) in the control group, resulting in a highly significant group difference (P < 0.001 ). Conclusion . Patients participating in a mindful walking program showed reduced psychological stress symptoms and improved quality of life compared to no study intervention. Further studies should include an active treatment group and a long-term follow-up.